Implementation of ESG Principles in Investment of Bank Syariah Indonesia: An Analysis of Maqashid Shariah - Putri; Purwanto; M. Pudail (Mutanaqishah: Journal of Islamic Banking, 2025)
Purpose – This study aims to analyze the application of the principles of Enveromental, social, Governance (ESG) in the investment of Indonesian Islamic banks (BSI) in terms of maqashid syariah perspective. Methodology – The method used in this research is a qualitative method with a descriptive approach. The data sources used come from secondary data in the form of annual reports, industry reports, and online news. In addition, the research data also comes from various articles published in scientific journals. Findings – The results of this study indicate that there is a strong alignment between the principles of ESG and Maqashid sharia in investment activities carried out by Bank Syariah Indonesia (BSI). The alignment of these two concepts creates an investment model that is not only focused on financial gain but also oriented towards mutual benefit and environmental preservation. This research identifies the ESG principles in the investments made by BSI in line with maqashid sharia for the protection of life (hifs al-nafs), reason (hifz al-aqal), property (hifz al-maal), religion (hifz al-din) and offspring (hifz al-nas). Implications – The implication of this research is that the ESG principle in investment activities if done properly does not conflict with the maqashid syariah principle. Originality – This research provides a new perspective on the alignment between ESG principles and maqashid sharia. The results of this study provide data support that these two concepts complement each other, so that investments do not only consider financial returns.